Pengaruh Penambahan Variasi Starter Terhadap Kualitas dan Lama Proses Pengomposan dengan Metode Takakura - Vita Kumalasari (STIKes Surya Global Yogyakarta, 2018)
This research is done to support government programs to improve community empowerment in agriculture, by making gapoktan. The obstacles faced by urban communities are limited land, making it difficult to obtain land as a planting medium. Composting process with a simple and fast method also does not require a large area of land in order to get the planting medium. Therefore, this research is indispensable. This study is aimed to determine the effect of adding a variety of starter to the length of the composting process and the quality of the resulting fertilizer. This research was a research using descriptive qualitative design. In this research, there were three treatments, i.e. without starter (control) and with starter EM4 and MOL tape. The research analyzes include the length of composting, color, aroma, temperature, C, N, P, K and C / N ratio. The results showed that the best treatment was on making compost using MOL tape starter. Within 4 days, the compost added MOL tape would change color to blackish, crumb and smelling the soil. This compost contains 0.47% of total phosphorus, 1.67% of total potassium, 0.51% of total nitroge, 25.73 organic carbon and 13.25 C/N Ratio. These results indicated that compost made using MOL tape starter meets SNI19-7030-2004 regarding compost specification from domestic organic so that it can be used as compost.